The island of Dr. Libris - Grabenstein, Chris (Random House, 2015)
A twelve-year-old boy, worried that his parents may divorce, discovers that an island in the middle of the lake where he is spending the summer is the testing grounds of the mysterious Dr. Libris, who may have invented a way to make the characters in books come alive.